Impact dimensions the Training process of the in components intellectual capital: Exploratory search in the National Insurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The concept of training is no longer traditionally understood Limited organize traditional training courses, but has become a strategic choice in the investment and development of human resources system, attic trying to find the answer to the core problem of the study whichis the extent to which the training process, the traditional form that meets the needs of the company the development of intellectual capital.This research aimstostatementof the impact dimensions the training process(training role, support or top management , training programs, modern technology)of the in components Intellectual Capital(Human Capital, Structural Capital, Customer Capital) and provide the top management of the Company for the development of scientific perception of the current training methods and the development of skills, abilities and experience of its employees, in order to achieve the company's goals.To achieve the aim of the research was selected national insurance company center locations to conduct research and sample consisted search of a group of experts and directors of departments and branches of the company, was information on the sample using a questionnaire and annual reports of the Company collection, data were treated using a combination of statistical methods, including measures of central tendency specifically, the arithmetic mean, standard deviation, and calculating the correlation between research and the impact of using the Pearson correlation coefficient measure variables.In light of the findings and analyzes the researcher to a group of the most important conclusions therearemoral and the impact of trainingprocess dimensionsin intellectual capital in general relationship.Based on the conclusions researcher presented a set of recommendations of the most important, the adoption of the top management of the training process as an urgent and ongoing need to aim to develop human resource and this should raise the level of training programs and development of intellectual capital in the company.